1993
DOI: 10.1002/bjs.1800800136
|View full text |Cite
|
Sign up to set email alerts
|

Controlled trial of wound infiltration with bupivacaine for postoperative pain relief after appendicectomy in children

Abstract: A double-blind controlled trial was performed to assess the effectiveness of wound infiltration with bupivacaine for postoperative pain relief after appendicectomy in children. Sixty children entered the trial and 52 completed it; they were randomized to receive bupivacaine or placebo. Assessment of postoperative pain using a numerical scoring system was made by the child, the recovery sister and the ward sister, and by measurement of the time between the end of the operation and the need for narcotic injectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 5 publications
0
24
0
Order By: Relevance
“…In a previous study, two of the authors of this study found no evidence of reduced postoperative pain when 0.25% bupivicaine was applied topically to sockets immediately on extraction of teeth under general anaesthesia 7 . Local anaesthesia, however, has been used for other surgical procedures with good effect 3,25 . Over the last decade, the practice of using general anaesthesia for dental extractions has been scrutinized in the UK by the dental and anaesthetic professionals, especially in relation to safety.…”
mentioning
confidence: 99%
“…In a previous study, two of the authors of this study found no evidence of reduced postoperative pain when 0.25% bupivicaine was applied topically to sockets immediately on extraction of teeth under general anaesthesia 7 . Local anaesthesia, however, has been used for other surgical procedures with good effect 3,25 . Over the last decade, the practice of using general anaesthesia for dental extractions has been scrutinized in the UK by the dental and anaesthetic professionals, especially in relation to safety.…”
mentioning
confidence: 99%
“…However, it is known that the postoperative analgesic needs of adult patients and pediatric patients undergoing appendectomy are different, and it is not appropriate to consider the studies done in adult patients correspond exactly to those performed in pediatric patients (24) . As a matter of fact, Wright et al (25) showed in a controlled study of appendectomized children, bupivacaine infiltration significantly reduced postoperative pain. In our study, we think that reaching the same pain level of LA group in the OA group depends on the local bupivacaine effect.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is well established that interleukin-6 (IL-6) released during abdominal surgery is a sensitive marker of tissue damage induced by mechanical or thermal injury [4,8,11,14,40]. The injury provoked by insufflation of dry gas might be one reason why there are no overall significantly different trauma response levels between open and laparoscopic surgery [3,11,14,15,18,20,22,41].…”
Section: Humidity Of Gasmentioning
confidence: 99%
“…Local anesthesia, preferably administered into the incision of access before the wound is created, is recommended by many authors, with significant pain reduction in both open [14,41] and laparoscopic procedures [26]. Not all studies have shown a significant difference however [1,7,13].…”
Section: Operation Factorsmentioning
confidence: 99%